2012
DOI: 10.1007/s10870-012-0300-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Halogen Bonding in Crystal Structures of 3-Halogeno Cytisine Derivatives

Abstract: The crystal structures of three 3-halogeno derivatives of 13N-substituted cytisine have been determined by X-ray diffraction. The two 13-acetyl substituted compounds, 3-bromo (1) and 3-iodo (2) are isostructural, with the isostructurality index as high as 99%. They both crystallize in monoclinic P2 1 space group, with unit cell parameters of a = 8.4709(10) Å , b = 9.2266(12) Å , c = 8.6051(10) Å , b = 98.528 (11)8 (1) and a = 8.2322(6) Å , b = 9.1724(7) Å , c = 8.5494(6) Å , b = 98.181 (7)8 (2). In turn, 3-bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…While examples of chloride, bromide, and iodide as XB acceptors are known, 148,207 only one report of fluoride exists. 208 Farnham, Dixon, and Calabrese's study on fluoride showed that discrete ion pairs were formed when pentafluorophenyl iodide was used as the XB donor. However, a polymeric chain could be formed when ditopic diiodooctafluorobutane was used as the XB donor with fluoride bridges.…”
Section: Tautomeric Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…While examples of chloride, bromide, and iodide as XB acceptors are known, 148,207 only one report of fluoride exists. 208 Farnham, Dixon, and Calabrese's study on fluoride showed that discrete ion pairs were formed when pentafluorophenyl iodide was used as the XB donor. However, a polymeric chain could be formed when ditopic diiodooctafluorobutane was used as the XB donor with fluoride bridges.…”
Section: Tautomeric Controlmentioning
confidence: 99%
“…A number of groups have prepared remarkable solid-state architectures with XB as the predominant intermolecular interaction responsible for the stability of these structures. In addition to the above examples, chains are formed with bis­( N -heterocycle)­diacetylenes with ditopic iodo donors and with bifunctional molecules (containing both XB donor and acceptor moieties) that displayed remarkable synthon robustness in the presence of typically structure-destabilizing and bulky substituents. The formation of chainlike structures is useful in the preparation of materials with conducting and magnetic properties as well as noncentrosymmetric crystals capable of second harmonic generation in optical devices.…”
Section: Halogen Bonding In the Solid Statementioning
confidence: 99%
“…Despite these conditions, large amounts of unreacted protected cytisine were Recently, the crystal structures of N-acetyl-9-bromocytisine 110a, N-acetyl-9-iodo cytisine 119a, and N-Boc 9-bromocytisine 107a have been determined by X-ray diffraction. 132 In the N-acetyl derivatives, the molecules are connected by relatively strong interactions C−X•••O. These interactions are weak in the N-Boc bromo derivative 107a but contribute nevertheless to organize the two-dimensional structure.…”
Section: Successive Formation Of Rings C Then Amentioning
confidence: 99%
“…Recently, the crystal structures of N -acetyl-9-bromocytisine 110a , N -acetyl-9-iodo cytisine 119a , and N -Boc 9-bromocytisine 107a have been determined by X-ray diffraction . In the N -acetyl derivatives, the molecules are connected by relatively strong interactions C–X···O.…”
Section: (−)-Cytisine Derivatives: Synthesis and Propertiesmentioning
confidence: 99%